ANALISIS GAMBARAN KEPEMIMPINAN TRANSFORMASIONAL, WORK ENGAGEMENT DAN PERILAKU KERJA INOVATIF KARYAWAN - Kania, Dewi; Senen, Syamsul Hadi; Masharyono, Masharyono (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study is to see the description of transformational leadership, work engagement and innovative work behaviorDesign/methodology/approachh - The design of this study was cross sectional method. This research uses descriptive approach with explanatory survey method. The analysis research unit is employees of PT. Jasa Marga Purbaleunyi Bandung Branch as much 82 people. Data collection using questionnaire. The analysis technique used is descriptive technique by using frequency distributionFindings - Based on the results of the research using descriptive analysis, the results obtained that transformational leadership in the quite effective category, work engagement in the quite high category, and innovative work behavior in the high category. Originality/value -Â The differences in this study located on an object research , time research , a measuring instrument , literature that used , the theory that is used and the results of the study.